S-BPM ONE - Running Processes : 5th International Conference, S-BPM ONE 2013, Deggendorf, Germany, March 11-12, 2013. Proceedings - Schneeberger, Josef; Fischer, Herbert (Communications in Computer and Information Science, 2013)
This book constitutes the thoroughly refereed proceedings of the 5th International Conference on Subject-Oriented Business Process Management, S-BPM ONE 2013, held in Deggendorf, Germany, in March 2013. The papers are organized in topical sections on running concepts; running business process management types; running applications; running ideas; running solutions; running projects.